Febuxostat-induced agranulocytosis in an end-stage renal disease patient: A case report. Issue 2 (January 2017) - Poh, Xue Er; Lee, Chien-Te; Pei, Sung-Nan
Abstract: Introduction: Febuxostat, a nonpurine xanthine oxidase inhibitor, is approved as the first-line urate-lowering therapy in gout patients with normal renal function or mild to moderate renal impairment. The most common adverse effects of febuxostat are liver function test abnormalities, diarrhea, and skin rash. However, there is insufficient data in patients with severe renal impairment and end-stage renal disease (ESRD). We report the first case, to our knowledge, in which agranulocytosis developed after febuxostat treatment in an ESRD patient. Clinical presentation: A 67-year-old woman with gout and ESRD received febuxostat 40 mg a day for 2.5 months. She subsequently complicated with febrile neutropenia and the absolute neutrophil count was only 14/μL. After broad-spectrum antibiotics treatment and no more exposure to febuxostat for 17 days, her infection and neutrophil count recovered. Bone marrow study during neutropenic period showed myeloid hypoplasia without evidence of hematologic neoplasms. Conclusion: As febuxostat use may become more common in the population of advanced renal failure, clinicians should be aware of this rare but potentially life-threatening adverse effect. Based on our experience, close monitoring hemogram and immediate discontinuation of this medication may prevent serious consequences.